STUDI KASUS KECEMASAN BELAJAR PADA REMAJA - Sidik, Wahid Ammar; Noor, Marzuki; Muzni, Achmad Irfan (Universitas Muhammadiyah Metro, 2023)
The purpose of this study is to find out the description of learning anxiety in adolescents at SMP Muhammadiyah 1 Metro in the 2020/2021 academic year; knowing the factors that cause learning anxiety in adolescents at SMP Muhammadiyah 1 Metro in the 2020/2021 academic year. Knowing the impact of learning anxiety on adolescents at SMP Muhammadiyah 1 Metro in the 2020/2021 academic year. it can be concluded that the description of student anxiety experienced by students at SMP Muhammadiyah 1 Metro seen from its physical characteristics are sweaty hands, body shaking and weakness, hot cold, heart beating fast. In addition, the characteristics experienced are the behavior of avoiding teacher questions, in learning students daydreaming, and concentration. Based on the research findings, the factors that cause students' anxiety are the abilities of students, parental demands, and unsupportive health conditions while studying. The impact experienced by students when experiencing learning anxiety is in the form of a positive impact, namely increasing motivation to continue learning, improving self-efficacy, not repeating the same mistakes, and changing the way of learning. While the negative impact is learning outcomes that are less than optimal. Efforts made by teachers in reducing learning anxiety are by holding individual counseling, increasing students' learning motivation, and increasing self-confidence in completing learning tasks.